M-learning and autonomous education: the impact of the Moroccan digital classroom project on science subject’s learning - Boudine, Hommane; Sajid, Hassan; Bentaleb, Meriem; Tayebi, Mohamed; El Karfa, Driss (International Journal of Civilizations Studies & Tolerance Sciences, 2024)
The widespread adoption of pedagogical digitalization and its integration into teaching practices has been proposed in response to the global health crisis triggered by the COVID-19 coronavirus pandemic. This suggestion, aimed at ensuring inclusivity and equal opportunities among learners, has profoundly influenced education. In 2021, the Moroccan Minister of National Education for Preschool and Sport announced a significant step forward by launching the digital classroom project, combining distance and face-to-face learning models with digital tools to guarantee the continuity of educational systems in Moroccan institutions. The project specifically aims to strengthen the learning of science subjects (Mathematics, Life and Earth Sciences, and Physics) to secure ongoing education in the face of potential future disruptions. This digital pedagogical revolution has emerged as a highly suitable learning method for diverse social groups (such as people with disabilities and refugees) and various challenging circumstances (natural disasters, wars, pandemics…). The research outlined in this context seeks to assess the impact of combining the use of Artificial Intelligence (AI) and digital classrooms on the performance of science subjects in the Rabat Sale Kenitra region, providing insights into the evolving educational landscape.
Keywords: Artificial intelligence (AI); Digital classroom project; M-Learning; Pedagogical Digitalization